The Association Between P3 Amplitude at Age 11 and Criminal Offending at Age 23 - Gao, Yu (Journal of clinical child and adolescent psychology, 2013)
Reduced P3 amplitude to targets is an information-processing deficit associated with adult antisocial behavior and may reflect dysfunction of the temporal-parietal junction. This study aims to examine whether this deficit precedes criminal offending. From a birth cohort of 1,795 children, 73 individuals who become criminal offenders at age 23 and 123 noncriminal individuals were assessed on P3 amplitude. The two groups did not differ on gender, ethnicity, and social adversity. P3 amplitude was measured over the temporal-parietal junction during a visual continuous performance task at age 11, together with antisocial behavior. Criminal convictions were assessed at age 23. Reduced P3 amplitude at age 11 was associated with increased antisocial behavior at age 11. Criminal offenders showed significantly reduced P3 amplitudes to target stimuli compared to controls. Findings remained significant after controlling for antisocial behavior and hyperactivity at age 11 and alcoholism at age 23. P3 deficits at age 11 are associated with adult crime at age 23, suggesting that reduced P3 may be an early neurobiological marker for cognitive and affective processes subserved by the temporal-parietal junction that place a child at risk for adult crime